An input on the characterization of timber frame structural system of tabique walls - Pinto, Jorge (2014)
Tabique construction corresponds to a relevant Portuguese heritage. Urban and rural tabique construction exists all over the country. This traditional building technique started to be in disuse after the massive introduction of the reinforced concrete. Therefore, tabique buildings are already aged and, in general, they show signals of degradation. Recent research works have concluded that this degradation stage is essentially caused by the absence of a regular proper maintenance process. The fact that tabique buildings are mainly private property, that there are economical limitations and that there is still a lack of knowledge concerning this traditional building technique, have been the main reasons identified. In order to contribute solving this problem this paper intends to give an input on the characterization of timber frame structural system of tabique walls. In fact, a tabique building element is a structural system formed by a timber frame coated with an earthy render. The elements of the timber frame are nailed to each other. It has been noticed that there are different types of timber frames. Given technical information related to these alternative traditional structural solutions may be helpful in future rehabilitation processes. At the same time, the relevance of this information is even more expressive taking into account the following aspects: a) the access of this type of buildings is in general limited because they are private properties; b) they have been abandoned and, therefore, they are not accessible; c) they became a ruin and they are not safe to be accessed; d) they were demolished.